Analysis and Evaluation of a Quasi-Passive Lower Limb Exoskeleton for Gait Rehabilitation - Al-Hayali, Niaam Kh.; Nacy, Somer M.; Chiad, Jumaa S.; O. Hussein (Al-Khwarizmi Engineering Journal, 2021)
Lower extremity exoskeletons can assist with performing particular functions such as gait assistance, and physical therapy support for subjects who have lost the ability to walk. This paper presents the analysis and evaluation of lightweight and adjustable two degrees of freedom, quasi-passive lower limb device to improve gait rehabilitation. The exoskeleton consists of a high torque DC motor mounted on a metal plate above the hip joint, and a link that transmits assistance torque from the motor to the thigh. The knee joint is passively actuated by spring installed parallel with the joint. The action of the passive component (spring) is combined with mechanical output of the motor to provide a good control on the designed exoskeleton while walking. The results show that muscles’ efforts on both the front and the back sides of the user’s leg were decreased when walking using the exoskeleton with the motor and spring.